2018
DOI: 10.3390/molecules23061368
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship and Molecular Docking of Natural Product Library Reveal Chrysin as a Novel Dipeptidyl Peptidase-4 (DPP-4) Inhibitor: An Integrated In Silico and In Vitro Study

Abstract: Numerous studies indicate that diets with a variety of fruits and vegetables decrease the incidence of severe diseases, like diabetes, obesity, and cancer. Diets contain a variety of bioactive compounds, and their features, like diverge scaffolds, and structural complexity make them the most successful source of potential leads or hits in the process of drug discovery and drug development. Recently, novel serine protease dipeptidyl peptidase-4 (DPP-4) inhibitors played a role in the management of diabetes, obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 30 publications
1
46
0
Order By: Relevance
“…Since it was already proven that garlic extract inhibits DPP-4, and the main compounds in this extract are the ones mentioned above, this led us to hypothesize that these phytochemicals could probably inhibit DPP-Among these compounds, polyphenol catechin was already proven to inhibit DPP-4 [65]. To understand the potential DPP-4 inhibition of the remaining identified phytochemicals in garlic extract, in silico methodologies such as field-based virtual screening and molecular docking simulations were carried out based on our earlier works [44,66], where the qualitative structure-activity relationship model of DPP-4 inhibitors was constructed and validated experimentally. The prebuilt QSAR model was utilized to demonstrate the potential DPP-4 inhibition capacity of the identified phytochemicals in garlic bulb extract.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since it was already proven that garlic extract inhibits DPP-4, and the main compounds in this extract are the ones mentioned above, this led us to hypothesize that these phytochemicals could probably inhibit DPP-Among these compounds, polyphenol catechin was already proven to inhibit DPP-4 [65]. To understand the potential DPP-4 inhibition of the remaining identified phytochemicals in garlic extract, in silico methodologies such as field-based virtual screening and molecular docking simulations were carried out based on our earlier works [44,66], where the qualitative structure-activity relationship model of DPP-4 inhibitors was constructed and validated experimentally. The prebuilt QSAR model was utilized to demonstrate the potential DPP-4 inhibition capacity of the identified phytochemicals in garlic bulb extract.…”
Section: Resultsmentioning
confidence: 99%
“…Results revealed all the chemicals maintained a novelty score of very high, and Table 1 shows the similarity score of the identified phytochemicals predicted by the QSAR model for DPP-4 inhibition. The activity cliff summary of positive and negative electrostatic features of the identified phytochemicals such as the DPP-4 inhibitor is shown in Figure 7, compared to already-built QSAR features of DPP-4 inhibition [44,66]. The red color site represents positive electrostatics features, and blue color denotes negative electrostatic features of DPP-4 inhibition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kalhotra et al [30,31] examined the profile for the addition of hydroxyl groups to inhibit the DPP-4 enzyme. Their results showed that galangin (a flavonoid with two hydroxyl groups) gives higher inhibition than chrysin (a flavonoid with two hydroxyl groups).…”
Section: Stellasterol In Silico Study For Dpp-4 Enzymementioning
confidence: 99%
“…Absorption, Distribution, Metabolism, Excretion and Toxicity (ADMET) properties of DHF derivative molecules were analyzed using Accelery Discovery Studio (DS) 3.5 41,42 . Further, the docking studies were carried out using Biosolve IT (Lead IT) software package 43 and Desmond v3.6 Package was used to run the MD simulation. The intermolecular interactions were analyzed using Pymol and Chimera 44,45 .…”
Section: Methodsmentioning
confidence: 99%